Mind‐Mindedness and Theory of Mind: Mediating Roles of Language and Perspectival Symbolic Play. Issue 5 (24th February 2013) - Meins, Elizabeth; Fernyhough, Charles; Arnott, Bronia; Leekam, Susan R.; de Rosnay, Marc
Abstract : Relations among indices of maternal mind‐mindedness (appropriate and nonattuned mind‐related comments) and children's: (a) internal state vocabulary and perspectival symbolic play at 26 months ( N = 206), and (b) theory of mind (ToM) at 51 months ( n = 161) were investigated. Appropriate comments were positively associated with ToM, but were unrelated to internal state language and perspectival symbolic play. Nonattuned comments were negatively correlated with internal state language and perspectival symbolic play, but were unrelated to ToM. Path analyses indicated that the best fit model assumed: (a) indirect links between nonattuned comments and ToM via children's perspectival symbolic play, (b) a direct link between appropriate comments and ToM, and (c) an indirect link between appropriate comments and ToM via children's concurrent receptive verbal ability.